A Severe Case of Lupus Cerebritis. (5th December 2022) - Szewczyk, Christopher; Gonzalez, Hemil
Abstract : Objective: Lupus cerebritis is a rare but potentially fatal complication of SLE. Prompt diagnosis and rapid initiation of therapy can prove lifesaving. Background: We present the case of a 31-year-old woman who presented to the emergency department with one week of fevers, headaches and confusion. Review of systems was notable for diffuse muscle and joint pains, weakness and a rash. SLE and Sjogren's were both diagnosed six months prior to admission and treatment included prednisone, methotrexate, and hydroxychloroquine. She self-discontinued therapy six weeks prior to seek natural remedies in her native Ecuador. Vitals on admission were 102.2 F, 111 beats/min, 96/67 mmHg, 16 breaths/min and 95% SO2 on 2 L/min via nasal cannula. Physical exam was notable for conjunctival injection, hypopyon (OD), and oral ulcers with visible bleeding. Pelvic exam showed shallow ulcerations of the vaginal mucosa. Neurological exam was significant for diffuse weakness. There were punched-out ulcers on the digits of both hands. Laboratory markers of lupus disease activity were markedly abnormal. An MRI of the brain showed numerous punctate foci of restricted diffusion in the supra and infratentorial brain parenchyma. Few of the lesions showed subtle rim-enhancement and microhemorrhagic foci. CSF analysis showed 220 WBC/mL (70% PMNs), glucose 13 mg/dL and protein 63.7 mg/dL. No CSF oligoclonal bands were detected. CSF/serum albumin index showed mild impairment of the blood brain barrier. Cultures of CSF, blood, urine and sputum showed no growth. Design/Methods: NA. Results: The patient improved significantly upon initiation of pulsed corticosteroids, plasma exchange, and cyclophosphamide. She was transitioned to steroid-sparing agents and is doing well. Conclusions: Lupus cerebritis can be the dominant syndrome in a patient presenting with uncontrolled SLE. Imaging and CSF findings can be dramatic and evoke infectious syndromes. Once alternative diagnoses have been ruled out lupus cerebritis should be managed aggressively to ensure good outcomes.